The Role of New Technological Opportunities and the Need to Evaluate the Activities Performed in the Prevention of Diabetic Foot with Exercise Therapy - Piergiorgio Francia; Alessandra De Bellis; Giulia Iannone; Rosy Sinopoli; Leonardo Bocchi; Roberto Anichini (Medicines, 2021)
The diabetic foot (DF) is one of the most feared conditions among chronic complications of diabetes, which affects a growing number of patients. Although exercise therapy (ET) has always been considered a pillar in the treatment of patients at risk of DF it is not usually used. Several causes can contribute to hindering both the organization of ET protocols for Diabetes Units and the participation in ET programs for patients at different levels of risk of foot ulceration. The risk of favoring the occurrence of ulcers and the absence of clear evidence on the role played by ET in the prevention of ulcers could be considered among the most important causes leading to the low application of ET. The increased availability of new technologies and in particular of systems and devices equipped with sensors can enable the remote monitoring and management of physical activity performed by patients. Consequently, they can become an opportunity for introducing the systematic use of ET for the treatment of patients at risk. Considering the complexity of the clinical conditions that patients at risk or with diabetic foot ulcer can show, the evaluation of how patients perform the ET proposed can consequently be very important. All this can contribute to improving the treatment of patients and avoiding possible adverse effects. The aim of this brief review was to describe that the use of new technologies and the assessment of the execution of the ET proposed allows an important step forward in the management of patients at risk.